Epidemiologic Trends in Oculoplastics-Related Emergency Department Visits in the United States, 2006–2015. Issue 2 (March 2022) - Ahmad, Meleha; Zhao, Jiawei; Iftikhar, Mustafa; Canner, Joseph K.; Rajaii, Fatemeh; Mahoney, Nicholas; Zafar, Sidra; Woreta, Fasika
Abstract : Purpose: To characterize demographics and trends in oculoplastics-related emergency department (ED) visits. Methods: The authors conducted a retrospective, multiyear study of the nationwide ED sample database. The nationwide ED sample was queried for oculoplastics-related International Classification of Disease-ninth revision codes identified from a comprehensive list and categorized based on anatomic location, urgency, and trauma status. Demographics, clinical characteristics, procedure requirement, and cost data were analyzed. Variables associated with inpatient admission were assessed using univariate and multivariate logistic regression. Results: The authors identified an estimated 4.2 million ED visits in the United States with oculoplastics-related primary diagnoses, of which pathology was 80.8% eyelid/adnexal, 17.4% orbital, and 1.74% lacrimal. Overall, 31.3% of the visits were deemed to be nonurgent. Orbital pathology was more likely to be caused by trauma (70.6%), to be urgent (98.0%), and to require a procedure (45.6%) ( p < 0.001). While less than 5% of all patients required hospitalization, predictors for inpatient admission were urgent diagnoses (odds ratio, 14.9; CI, 13.7–16.1), presentation to a level 1 trauma center (odds ratio, 3.19; CI, 2.7–3.79), and presence of orbital pathology (odds ratio, 6.09; CI 5.73–6.47). Incidence of ED visits decreased in all categories; however, total inflation-adjusted charges increased. Conclusions: Over half of oculoplastics-related ED visits are for trauma, with orbital pathology being less common but requiring a high level of care. Although trends show a potentially decreasing incidence of oculoplastics-related ED visits, increasing costs and high proportion of nonurgent visits pose an opportunity for mitigating periocular trauma and increasing outpatient access to care, respectively. Abstract : The authors used a national representative database to identify patients with oculoplastics-related diagnoses seen in emergency departments across the United States from 2006 to 2015, finding a rising cost but decreasing incidence of these diagnoses.